Multiple functions of heterogeneous nuclear ribonucleoproteins in the positive single-stranded RNA virus life cycle - Wang, Jingming; Sun, Di; Wang, Mingshu; Cheng, Anchun; Zhu, Yukun; Mao, Sai; Ou, Xuming; Zhao, Xinxin; Huang, Juan; Gao, Qun; Zhang, Shaqiu; Yang, Qiao; et al. (Frontiers in Immunology, 2022)
The heterogeneous nuclear ribonucleoproteins (hnRNPs) are a diverse family of RNA binding proteins that are implicated in RNA metabolism, such as alternative splicing, mRNA stabilization and translational regulation. According to their different cellular localization, hnRNPs display multiple functions. Most hnRNPs were predominantly located in the nucleus, but some of them could redistribute to the cytoplasm during virus infection. HnRNPs consist of different domains and motifs that enable these proteins to recognize predetermined nucleotide sequences. In the virus-host interactions, hnRNPs specifically bind to viral RNA or proteins. And some of the viral protein-hnRNP interactions require the viral RNA or other host factors as the intermediate. Through various mechanisms, hnRNPs could regulate viral translation, viral genome replication, the switch of translation to replication and virion release. This review highlights the common features and the distinguish roles of hnRNPs in the life cycle of positive single-stranded RNA viruses.